2018
DOI: 10.1155/2018/4580921
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of Stretchable Electrodes by Sedimentation of Ag Nanoparticles in PDMS Matrix

Abstract: This study reports a facile fabrication method for highly conductive stretchable electrodes composed of a conductive 0D nanomaterial filler and an elastomer matrix. The local volume fraction of the Ag nanoparticles at the composite surface could be significantly increased by the sedimentation of Ag nanoparticles in uncured polydimethylsiloxane (PDMS) fluid. The stretchable electrodes had a surface resistance of 0.910 ± 0.509 Ω/sq and were stretchable up to 100% of strain without the reduction of the electrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…These low sheet resistance and resistivity prove that as-printed flexible and wearable conductors have excellent conductivity. Compared with other PDMS-based composite conductors, although many conductive fillers (AgNPs, Ag nanowires, Cu nanowires, or Au nanowires) were used to enhance the conductivity of the flexible composite, their conductance is relatively lower owing to the existence of PDMS. For example, Alexandre Larmagnac et al reported that conductive tracks were fabricated by screen-printing the composite ink of PDMS and Ag nanowires, and the traces exhibited a relatively low conductivity of 18,168 S cm –1 (∼1/35 of bulk conductance) . Furthermore, these printed Cu layers manifested outstanding thermal stability.…”
Section: Resultsmentioning
confidence: 99%
“…These low sheet resistance and resistivity prove that as-printed flexible and wearable conductors have excellent conductivity. Compared with other PDMS-based composite conductors, although many conductive fillers (AgNPs, Ag nanowires, Cu nanowires, or Au nanowires) were used to enhance the conductivity of the flexible composite, their conductance is relatively lower owing to the existence of PDMS. For example, Alexandre Larmagnac et al reported that conductive tracks were fabricated by screen-printing the composite ink of PDMS and Ag nanowires, and the traces exhibited a relatively low conductivity of 18,168 S cm –1 (∼1/35 of bulk conductance) . Furthermore, these printed Cu layers manifested outstanding thermal stability.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, metal NPs, as 0D conductive nanomaterials, should be incorporated into elastomer matrix to obtain stretchable electrodes. For example, Kim et al 61 prepared highly conductive stretchable electrodes by introducing Ag NPs in the PDMS matrix. The resulting electrodes displayed a low surface resistance of 0.910 Ω sq −1 and a high stretchability up to 100% strain with minimal degradation in electrical conductivity.…”
Section: Electrodes For Fofetsmentioning
confidence: 99%
“…The ratio of base and curing agent for mixing, according to the documentation, is 10:1. This set was chosen as the basis (matrix) in many scientific articles [1,2,12,21], which made it a widely used model elastomer. HGM (Graphite PRO, Russia) with a bulk density of 0.19 g/cm 3 were used as a filler.…”
Section: Fabrication Of Composite Materialsmentioning
confidence: 99%
“…Polydimethylsiloxane (PDMS) is the most widely used silicon-based polymer due to its versatility and attractive properties [1,2]. In particular, PDMS is non-flammable, non-toxic, transparent, odorless, tasteless and colorless.…”
Section: Introductionmentioning
confidence: 99%